Non‐IgE‐mediated gastrointestinal allergies—Do they have a place in a new model of the Allergic March. Issue 2 (10th January 2019) - Meyer, Rosan; Fox, Adam T.; Chebar Lozinsky, Adriana; Michaelis, Louise J.; Shah, Neil
Abstract: The rise in food allergy has been described as the "second wave" of the allergy epidemic, with some developed countries reporting a prevalence of 10% of challenge‐proven food allergies. Recognition of the Allergic March has played a crucial role in identifying causality in allergic conditions, linking atopic dermatitis to food allergy and food allergy to other atopic disorders, thereby highlighting opportunities in prevention and the importance of early intervention. This publication will establish the value of weaving the less well‐understood, non‐IgE‐mediated food allergy into the Allergic March and mapping its progression through childhood and its associated co‐morbidities. The proposed non‐IgE‐mediated Allergic March highlights the concomitant presentation of gastrointestinal symptoms and atopic dermatitis as early presenting symptoms in confirmed non‐IgE‐mediated allergies and the later development of atopic co‐morbidities, including asthma and allergic rhinitis, similar to the IgE‐mediated Allergic March. This publication highlights recent observations of a link between non‐IgE‐mediated food allergy in early childhood and functional gastrointestinal disorders in later life and also the reported occurrence of extra‐intestinal manifestations at later ages. Although significant limitations exist in regard to the proposed evolution of the Allergic March model, the authors hope that this publication will influence the management of non‐IgE‐mediated gastrointestinal allergies and inform future research and interventions.